Veterinarians Experience Animal Welfare Control Work as Stressful - Väärikkälä, Sofia; Hänninen, Laura; Nevas, Mari (Frontiers in Veterinary Science, 2020)
The aim of the study was to evaluate the job satisfaction of official veterinarians working in the field of animal welfare control and identify both positive features and challenges of their work. An electronic questionnaire was designed to evaluate job satisfaction. The questionnaire was responded to by 73 of the 98 Finnish official veterinarians working in the field of animal welfare control. The Spearman’s rank correlation coefficient was used to evaluate the relation between stress and different work-related factors. More than half of the respondents reported work-related stress or fatigue. Threatening situations, disturbed work–private life balance and a high amount of overtime work were found to be frequent underlying causes of stress. Fieldwork, especially when working alone, was perceived as the most challenging part of the work. Of the respondents, three out of four performed animal welfare inspections mainly alone. Although the respondents reported getting additional help to perform an inspection most of the times they needed it, a wish to work in a pair was highlighted. The results of the present study indicate that official veterinarians often experience work-related stress and fatigue. By testing interventions shown to be beneficial, such as providing adequate support within the work community, decreasing the workload and enabling inspections to be done in pairs, job satisfaction could be improved.